Polyploid nuclei in human artery wall smooth muscle cells. - Barrett, T B (1983)
Although polyploid nuclei have long been known to be present in many adult human tissues, the ploidy of smooth muscle cells in human artery wall has never been determined. We measured DNA content in individual smooth muscle cell nuclei of artery wall specimens by two means: Feulgen microdensitometry and flow microfluorimetry. A significant percentage of nuclei were polyploid; most of these were tetraploid, although higher levels were also found. The frequency of polyploidy varied with age from less than 1% at birth to a mean of 7% in adult aortic, carotid, and iliac vessels. Atherosclerotic plaques had a lower tetraploid content than the underlying media, whereas normal intima was similar to the corresponding media. The increase in frequency of hyperploid smooth muscle cell nuclei correlates with the normal growth, development, and aging of human artery wall. We suggest that the regular existence of a subset of polyploid smooth muscle cells may indicate an important functional role for this phenotype.